2007 4th IEEE International Symposium on Biomedical Imaging: From Nano to Macro 2007
DOI: 10.1109/isbi.2007.357032
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Conductivity Estimation Using Somatosensory Evoked Potentials and Cortical Constraint on the Source

Abstract: A new method for in vivo conductivity estimation of head tissues is proposed, in the case of a realistic piecewise constant model. Unlike classical electrical impedance tomography methods, for which the conductivity is inferred from a current injection on the scalp, we use an evoked source inside the brain that comes from a somatosensory experiment. The resulting uncertainty with respect to the source is then balanced by strong constraints : we assume the source to be a single dipole located in the cortex, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 11 publications
1
16
0
Order By: Relevance
“…This approach has been suggested in Lew et al (2007), Vallaghé et al (2007). In section 2 we use Cramer-Rao bounds to demonstrate the impracticality of this approach by showing that the uncertainty in the skull conductivity is inherent to the model.…”
Section: Introductionmentioning
confidence: 99%
“…This approach has been suggested in Lew et al (2007), Vallaghé et al (2007). In section 2 we use Cramer-Rao bounds to demonstrate the impracticality of this approach by showing that the uncertainty in the skull conductivity is inherent to the model.…”
Section: Introductionmentioning
confidence: 99%
“…This was extensively demonstrated in Plis et al (2007). This approach of extracting the conductivity together with the dipole location was also suggested in Lew et al (2007) and Vallaghé et al (2007).…”
Section: Traditional Eeg Inverse Problemmentioning
confidence: 83%
“…The obtained results showed that the estimation of the skull conductivity improves the estimation of the underlying brain activity, especially in the case of multiple active dipoles. In addition, the proposed method was compared with the optimization techniques introduced by Vallaghé et al [12] (that requires having only one dipole active) and Gutiérrez et al [10] (that requires knowing the active dipole positions in advance). The proposed method showed very competitive results for these examples.…”
Section: Discussionmentioning
confidence: 99%
“…The operator was calculated for ρ gt = 3.6 mS/m, and white noise was added to obtain SNR = 10 dB. The proposed method is compared with two other approaches: 1) our previous model [18] with a default value ρ fix = ρ m a x +ρ m i n 2 = 18.15 mS/m; and 2) the optimization method studied by Vallaghé et al [12] that is able to estimate ρ and the brain activity jointly since there is only one active dipole for this example. The estimated dipole locations are shown in Fig.…”
Section: A Synthetic Datamentioning
confidence: 99%
See 1 more Smart Citation